THE THEORETICAL STUDY OF CHARLES DICKENS’S WORKS - Gulmira Ahmadjonova Anvarjon qizi (TADQIQOTLAR, 2025)
Abstract. This paper examines the works of Charles Dickens through a theoretical lens, focusing on realism, social criticism, and moral humanism. Dickens’s novels have been analyzed from various theoretical perspectives, including moral philosophy, narrative theory, and psychological criticism. Using examples from Oliver Twist, A Tale of Two Cities, and David Copperfield, this study explores how Dickens combines realistic depiction with moral imagination to represent the social and emotional struggles of nineteenth-century England. The research also considers the symbolic and linguistic dimensions of his writing, emphasizing his contribution to literary realism and social reform. The findings highlight that Dickens’s fiction serves not only as artistic expression but also as a theoretical model for understanding humanity, society, and ethics.